Pengembangan Self-Management melalui PjBL untuk Meningkatkan Kemampuan Computational Thinking pada Pembelajaran Informatika Fase D: Penelitian - Natasya Titania Ramadhanti; Triyanna Widiyaningtyas; Satria Putra Pratama (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Purpose – This Classroom Action Research (CAR) aims to develop students’ self-management and enchance their computational thinking skills through the implementation of the Project-based Learning (PjBL) model in Informatics learning for Phase D. The study focuses on how PjBL can be used not only to improve cognitive skills, but also to promote personal responsibilities and autonomy in students’ learning. Methods – The study was conducted in two cycles, each comprising the stages of planning, action, observation, and reflection stages. The research subjects were seventh-grade students at a junior high school in Malang. Data were collected through multiple methods, including observation, interviews, and documentation, to ensure a comprehensive understanding of the learning process and outcomes. Findings – The findings indicate that the application of PjBL effectively improves students’ independence in managing time, tasks, and their own learning processes. Moreover, students demonstrated significant improvement in computational thinking skills. Research Implications – Based on the findings, PjBL has been proven to be an effective approach for enhancing meaningful learning experiences, foster active student engagement, and support the development of 21st-century skills.